2015
DOI: 10.1002/qj.2686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of initial perturbation methods for ensemble prediction at convective scale

Abstract: Convective-scale ensemble prediction systems (EPSs) are often initialized with downscaled initial condition perturbations (ICPs) from a global coarser EPS. Although downscaled ICPs have been shown to have a positive impact at short ranges, they cannot represent the uncertainty at small scales. Hence, there is a spin-up of around 9-12 h until the forecast perturbations develop realistic small-scale structures. On the other hand, ensemble data assimilation (EDA) is a common approach to obtain initial perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 33 publications
3
63
0
Order By: Relevance
“…Furthermore, the cool-start analysis systems, whereby the high-resolution backgrounds were spun up over 6 h, could potentially be improved. It is possible that the spinup process was incomplete at 6 h (e.g., Raynaud and Bouttier 2016), which may have negatively impacted the cool-start analyses. Thus, further work might examine spinup characteristics more closely and potentially lengthen the spinup period.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…Furthermore, the cool-start analysis systems, whereby the high-resolution backgrounds were spun up over 6 h, could potentially be improved. It is possible that the spinup process was incomplete at 6 h (e.g., Raynaud and Bouttier 2016), which may have negatively impacted the cool-start analyses. Thus, further work might examine spinup characteristics more closely and potentially lengthen the spinup period.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…It also has the advantage of being simple to implement and with low CPU costs. However, when compared to other CPU consuming methods it suffers from a spin‐up time of about 9–12 hr (Raynaud & Bouttier, ; Vié et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…9 are a maximum of only ten hours old, this may explain why a small-scale (3D-like) energy spectrum is not seen. Raynaud and Bouttier (2016) also showed that perturbations downscaled into the 2.5 km grid-length AROME EPS took 9-12 hours to develop into realistic small-scale structures. This issue may be particularly relevant to our case study due to the passage 25 of a cold front, as opposed to a case where convection is the dominant source of precipitation (the latter of which may generate 3D motion more quickly).…”
Section: ē (N )mentioning
confidence: 96%
“…Raynaud and Bouttier (2016)). Alternatively, a set of ensemble members that sample a climatological PDF may be taken from one long (e.g.…”
Section: Generating the 93 Convective-scale Ensemble Membersmentioning
confidence: 99%